Symptomatic Stenosis of the Cavernous Portion of the Internal Carotid Artery due to an Irresectable Medial Sphenoid Wing Meningioma: Treatment By Endovascular Stent Placement - Heye, S.; Maleux, G.; Van Loon, J.; Wilms, G. (American Journal of Neuroradiology, 2006)
SUMMARY:A 48-year-old woman, with right-sided proptosis and decreased visual acuity, presented with acute left sensorimotor deficit. Recent ischemia in the right posterior watershed area was found on CT and MR imaging, as well as a right-sided medial sphenoid wing meningioma causing high-grade stenotic encasement of the cavernous portion of the right internal carotid artery. Because the patient was symptomatic and complete resection of the meningioma was impossible, the stenosis was successfully treated with a balloon-expanding stent.